Chemical composition, antibacterial and antioxidant activities of essential oils from flowers, leaves and aerial parts of Tunisian Dittrichia Viscosa. Issue 6 (2nd November 2019) - Gharred, Nawres; Dbeibia, Amal; Falconieri, Danilo; Hammami, Saoussen; Piras, Alessandra; Dridi-Dhaouadi, Sonia
ABSTRACT: The objective of this work was to determine the chemical composition, the antioxidant and antibacterial activities of the essential oils (EOs) extracted by hydrodistillation from different organs of the D. viscosa : flowers, leaves and aerial parts. The main compounds identified by GC/MS are oxygenated sesquiterpenes. Among these compounds, ( E )-nerolidol (40.7%) is the most abundant constituent of flowers' essential oil while caryophyllene oxide (9.9%), isolongifolan-7-α-ol (10.3%) and α -eudesmol (9.1%) are the major constituents of the leaves' essential oil. The presence of these compounds in the aerial parts' essential oil is solely due to those of the flowers and leaves that constitute these aerial parts. The volatile extracts showed antioxidant effects with IC50 values ranging between 9.25 and 9.75 mg.mL −1 . On the other hand, EOs showed antibacterial effects on both Gram-positive and Gram-negative bacteria. The highest activity was obtained with flowers' essential oil against Enterococcus faecalis and Escherichia coli .